Overview of the use of digital pop-up book media to improve students’ preparedness for fire disasters at Islamic Boarding Schools in Jambi City: A Descriptive Study on Interactive Media-Based Disaster Education in Pesantren Settings - Subandi, Andi; Noerjoedianto, Dwi; Difa Septian Lestari, Tiara (Riset Informasi Kesehatan, 2025)
Background: Fire disasters pose a serious threat to students in school environments, particularly in Islamic boarding schools where fire prevention knowledge and emergency response preparedness are often limited. Innovative media, such as digital pop-up books, offer interactive learning experiences to enhance disaster awareness. Method: A descriptive quantitative study was conducted at Islamic boarding schools in Jambi City. A total of 60 students from grades 10 to 12 were selected using purposive sampling. Data were collected using a structured questionnaire based on LIPI–UNESCO preparedness indicators and analyzed using descriptive statistics. Results: The majority of students (56.7%) demonstrated a high level of preparedness after the educational session, while 33.3% were in the moderate category and only 10% remained in the low category. The digital pop-up book media was effective in improving understanding and readiness for fire emergencies. Conclusion: The use of digital pop-up book media is a promising method to improve students’ preparedness for fire disasters in Islamic boarding schools. It is recommended for inclusion in school-based disaster education programs.